2020
DOI: 10.1021/acssuschemeng.0c01311
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Acid–Base Ratio and Recycling on the Pretreatment Performance of the Protic Ionic Liquid Monoethanolammonium Acetate

Abstract: The use of protic ammonium ionic liquids (PILs) in the pretreatment of lignocellulosic biomass is a promising alternative to using expensive aprotic ionic liquids such as 1-ethyl-3-methylimidazolium acetate, [Emim]­[OAc]. In this work, the PIL monoethanolammonium acetate, [MEA]­[OAc], was used for the pretreatment of sugar cane bagasse. The study investigated changing the acid base ratio (ABR) from 0.1 to 10 and recycling of the solvent. We determined the lignin extraction, lignin recovery, solvent recovery, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 45 publications
0
22
0
5
Order By: Relevance
“…Saha et al (2017) reported lignin removal of 90.1% from bagasse using [EMIM]­OAc at the optimal pretreatment conditions: 2 h at 140 °C and ionic liquid to bagasse ratio equal to 20:1 (w/w). Although the studies use a high amount of IL in the pretreatment step, PILs can be recycled and reused at least three or four times, which shows the process is potentially economically feasible. ,, …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Saha et al (2017) reported lignin removal of 90.1% from bagasse using [EMIM]­OAc at the optimal pretreatment conditions: 2 h at 140 °C and ionic liquid to bagasse ratio equal to 20:1 (w/w). Although the studies use a high amount of IL in the pretreatment step, PILs can be recycled and reused at least three or four times, which shows the process is potentially economically feasible. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Another aspect that must be considered is the amount of water used to wash the biomass after pretreatment, as it influences the recovery cost of the PIL, which needs to be recycled to make the process viable . Studies in the literature have shown that the PIL can be recycled and reused in the pretreatment at least four times (>98%) without showing a decrease in lignin removal. ,,, Barcelos et al. (2021) using [Ch]­[Lys] PIL in pretreatment to produce ethanol reached an optimal design resulting in a predictable ethanol selling price of $3/gge and carbon footprint of 16.4 gCO 2e /MJ, an 82% reduction compared to gasoline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…189,190 In the ionoSolv process, 191 deconstruction of lignocellulose is conducted in low-cost (ca. $ 1-2 / kg) PILs, exemplified by 1-methylimidazolium chloride, [hmim][Cl], 192 [Et 3 NH][HSO 4 ], 193,194,195,196 198 at elevated temperatures, affording a cellulose rich pulp. In contrast, when low-cost tetramethylguanidinium (TMG) hydrogen sulfate was used, the biomass completely dissolved and the cellulose was precipitated with ethanol.…”
Section: Figure 17 Zwitterionic Liquids (Zils) That Dissolve Lignocel...mentioning
confidence: 99%
“…Numerous types of pre-treatments of lignocellulosic biomass have been developing for the release of sugars (e.g., hexoses and pentoses) for the production of 2G ethanol (Moraes et al 2015a). Alkaline pretreatments are common for the delignification of biomass, having additional effects on the silica removal (ash insoluble component) or the partial removal of hemicelluloses (including acetyl and uronic acid groups) and the swelling of cellulose, resulting in a substantial increase in the fiber surface (Carvalho et al 2016).The residues generated are potential sources for AD (Rabelo et al 2011), although little has been studied about the anaerobic co-AD, especially for the recent and innovative pre-treatment of biomass and hydrolysis, e.g., deacetylation process, pre-treatment with ionic liquids, hydrolysis using genetically modified yeast, among others (Nakasu et al 2020). The complexity of such substrates for AD may be one of the factors driving the integration of the 1G2G ethanol process by co-AD of its residues, e.g., with 1G vinasse that is already recognized as a substrate for biogas production (Ferraz Júnior et al, 2016).…”
Section: Introductionmentioning
confidence: 99%